Bioequivalence study of two formulations of 100 mg capsule of itraconazole - Manfio, Josélia Larger; dos Santos, Maurício Bedin; Favreto, Wagner Alex Jann; Weich, Anelise; Pugens, Ana Maria; Donaduzzi, Carmen Maria (Arzneimittelforschung, 2010)
The purpose of this study is to compare the bioavailability of two itraconazole (CAS 84625-61-6) capsule formulations. An open, randomized, two-period cross-over study with a 7-day washout interval was conduced in 32 healthy volunteers. The plasma samples were obtained up to 96 h after drug administration. A sensitive and specific liquid chromatography-tandem mass spectrometry (LC-MS/MS)method was developed and validated for the determination of itraconazole in human plasma. Itraconazole and ketocona-zole (internal standard) were extracted from the plasma by liquid-liquid extraction using diethylether: dichloromethane(70 : 30) as extraction solvent and separated on a C8 analytical column (150 mm × 4.6 mm I.D.) maintained at 40 °C. The elution was performed by a constant flow rate of 1.2 mL/min and the mobile phase consisted of acetonitrile and acetic acid 0.1% (85 : 15 v/v). The mass spectrometer equipped with an electrospray source in positive mode, was set up in multiple reaction monitoring, to detect parent → product ion 705.0 →392.0 (itraconazole) and 531.0 → 81.70 (ketoconazole). The chromatographic separation was obtained within 3.5 min and was linear in the concentration range of 5 to 600 ng/mL. Bioequivalence between the products was determined by calculating 90% confidence intervals for the ratio of Cmax (95.02%–109.48%), AUC0–t (81.41% – 107.77%) and AUC0–∞(80.85% – 106.86%). These values for the test and reference products are within the 80–125% interval, proposed by FDA and EMEA. It was concluded that the proposed method was successfully applied to a pharmacokinetic study in healthy human volunteers, and results showed that the two itraconazole formulations are bioequivalent in their rate and extent of absorption.
Keywords: Antifungal; CAS 84625-61-6; Itraconazole, bioequivalence, food-effect bioavailability; LC-MS/MS